Perencanaan Strategis Sistem Informasi pada Wyndham Opi Hotel Palembang - Desvilia Desvilia (Jurnal Sistem Informasi dan Ilmu Komputer, 2026)
This research aims to design an Information Systems and Information Technology (IS/IT) strategic plan for Wyndham OPI Hotel Palembang to support operational efficiency and enhance the quality of five-star hotel services. The study applies the Ward and Peppard framework, supported by analytical methods including Value Chain,PEST,SWOT,Critical Success Factors (CSF), MOST and McFarlan Strategic Grid. Through these approaches, the current IS/IT condition, challenges, and opportunities for digital system development within the hotel environment were mapped. The analysis reveals that although the hotel has implemented technologies such as SiteMinder and the Rhapsody management system, there is a need to improve self-service check-in capabilities, strengthen IT infrastructure, and maximize digital technology utilization. The proposed strategy recommends the development of an integrated self check-in system, enhancement of network infrastructure, and employee training through an LMS platform. This strategic plan is expected to support the hotel’s digital transformation to remain competitive in the modern hospitality industry.